A Self-Locking Knot for Lateral Fabellotibial Suture Stabilisation of the Cranial Cruciate Ligament Deficient Stifle in the Dog - McKee, W. M.; Miller, A. (Veterinary and Comparative Orthopaedics and Traumatology, 1999)
Maintaining adequate tension when knotting large diameter monofilament sutures can be challenging, especially without surgical assistance. A self-locking knot is described for lateral fabellotibial suture stabilisation of the canine cranial cruciate ligament deficient stifle. The self-locking knot enables maintenance of tension during tying and the knot can be tied by an unassisted surgeon. The inherent ability of the knot to maintain tension on the fabellotibial suture is due to the first throw of the knot creating a locking-loop effect. Increasing the tension on the suture material is readily achieved by applying traction on the free ends and tightening the first throw of the knot to remove the slack created. When the suture is tightened sufficiently four additional square throws are applied to the knot.A self-locking knot is described for lateral fabellotibial suture stabilisation of the canine cranial cruciate ligament deficient stifle. The inherent ability of the knot to maintain tension on the suture material is due to the first throw of the knot creating a locking-loop effect. Tension on the knot can be readily adjusted and the knot may be tied by an unassisted surgeon.
Keywords: Self-locking knot; lateral fabellotibial suture; cranial cruciate ligament